Managing stress for mental fitness - Raber, Merrill F. (Crisp Pub. Menlo ParkUS, 1993)
Defines stress, lists the 3 basic stages of stress, and provides suggestions for managing stress. Looks at understanding self and others; understanding and maintaining good health; and lists 10 steps for maintaining mental fitness.